Long-term outcomes and clinical phenotypes associated with best response to low dose alemtuzumab in cutaneous T-cell lymphoma - Cecilia Larocca; Ai-Tram N. Bui; John T. O’Malley; Anita Giobbie-Hurder; Marianne Tawa; Jessica E. Teague; Rachael A. Clark; Corey Cutler; Eric Jacobsen; David C. Fisher; Thomas S. Kupper; Nicole R. LeBoeuf (Blood Cancer Journal)
Abstract Cutaneous T-cell lymphomas (CTCL) have in common malignant T-lymphocyte infiltration in the skin. Low dose alemtuzumab (LDA) appears to be an effective treatment for leukemic disease, but in the absence of clinical trials, there is need for improved characterization of patients with CTCL most likely to benefit. A retrospective cohort study of 38 patients with CTCL treated with LDA with at least 5 years’ follow-up data was conducted. As a surrogate for a central memory T-cell (TCM) clinical phenotype, we evaluated whether the absence of a history of papules, plaques, and tumors (PPT) predicts better global and skin response. Twenty-five (65.8%) patients responded to LDA (95% CI: 49–80%). Patients with a TCM phenotype were more than eight times as likely to achieve a CR [OR: 8.2, 95% CI: 1.2–57.6]. CR rate in the skin was 81.8% in TCM phenotype patients compared to 37.0% in patients with a history of PPT (resident memory T-cell phenotype, TRM) [OR: 7.7, 95% CI: 1.4–42.7]. Three patients experienced any infection requiring systemic intervention. LDA monotherapy can safely produce exceptional response rates in those presenting with diffuse erythema but without a history of PPT.